Microbial Causatives of Diarrhea in Children in Erbil City - Al-Sorchee, Sawsan M Abdullah; Rabat, Abbas A; Juma, Intisar M (Al-Nahrain Journal of Science, 2013)
Five hundred samples of stool were colleted from patients with diarrhea (infants and children under ten years of age) admitted to the Pediatric and Maternity Hospital in Erbil City from March 2007 to September 2007. The samples were cultured on different culture media and according to the colony morphology, biochemical reactions and by the use of API 20E system, 35 (7%) E.coli I, 8 (1.6%) E.coli II, 17 (3.4%) E.coli III, 22 (4.4%) E.coli IV, 8 (1.6%) Shigella dysenteriae, 16 (3.2%) Salmonella arizonae, 12 (2.4%) Salmonella typhi and 6 (1.2%) Vibrio cholerae. In addition, cases of Entamoeba histolytica 175 (35%), Giardia lamblia 102 (20.4%) and Hymenolepis nana 2 (2.4%) were identified. No infectious agents were found in 75 (15%) of the samples. 22 (4.4%) of the samples had mixed infections. The sensitivity of the bacterial isolates to different antibiotics was performed. There was a variation in the resistance of the isolates ranging from 2-100% whereas other isolates were sensitive. Most cases of diarrhea were in children less than 3 years of age and the males (64%) had more infection rates than the females (35.8%). Children from urban (77%) areas had higher infection rates than those coming from rural (23%) areas. Children who were bottle fed (31.4%) had higher infection rates than those who were breast fed (17.6%) or those with mixed feeding (16.6%).